Analyses of 6G-network and Blockchain-network application security: future research prospect - Annas, Ammar Haziq; Zainuddin, Ahmad Anwar; Ramlee, Afnan Wajdi; Ya Omar, Ahmad Solihin; Md Saifuddin, Muhammad Hafiz Faruqi; Sidik, Nur Fatnin Izzati; Sapuan, Muhamad Syariff; Amerolazuam, Amysha Qistina; Hairul Nizam, Muhammad Haziq Zulhazmi; Mazlan, Farah; Omar, Nur Faizah; Abdul Rahman, Nur Alia Alina; et al. (IIUM Press, 2024)
The evolution from 5G to 6G signifies a monumental progression in wireless communication technology, promising enhanced capabilities and broader applications. Building on the transformative impact of 5G with its high speeds, low latency, and improved connectivity, the transition to 6G aims to overcome the limitations of its predecessor and unlock new potentials. However, this shift is not devoid of challenges, particularly concerning the privacy and security risks inherent in the adoption of 6G networks. Reflecting on the historical trajectory of wireless technologies, from the first 0G to the current 5G networks, each generational leap has brought significant enhancements in design, coverage, speed, quality of service, capacity, and latency rates. The ongoing deployment of 5G is expected to further expand network capacity through innovative architectural advancements, such as the convergence of information and communication technologies and the implementation of heterogeneous networks. These advancements are essential in optimizing energy consumption, enhancing overall performance, and ensuring the sustainability of wireless networks. Furthermore, the convergence of emerging technologies like the Internet of Things (IoT), energy harvesting, and Simultaneous Wireless Information and Power Transfer (SWIPT) is reshaping the landscape of wireless communication. These technologies not only facilitate the deployment of numerous low-power radios but also pave the way for a more interconnected and efficient wireless ecosystem. In this dynamic world of evolving wireless technologies, the concept of mobile edge computing (MEC) emerges as a novel paradigm for providing computing, storage, and networking resources at the edge of mobile networks. By allowing latency-sensitive and context-aware applications near end-users, MEC ensures efficient operations without compromising performance. This integration of edge computing within the Radio Access Network (RAN) architecture signifies a theoretical shift towards more distributed and responsive network infrastructures.